Potato Waste Reduction Mechanisms: A case study in Abshar district of Panjshir Province, Afghanistan - Mohammadi, Agha Mohammad; Mushair, Hasibullah; Habibi, Sayed Sanaullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
The objective of the current study is to estimate the amount of potato waste and introduce suitable mechanisms to reduce it in different stages of production. The investigation was done based on primary data in the year 2021-22 and Abshar district of Panjshir province was selected through cluster sampling process as study area. The data was collected through questionnaires which were distributed randomly to 40 farmers in the district. The results revealed that the average gross income, costs and net income of farmers was estimated around about 1941.55, 414,06 and 1527.49 US, respectively. Average production of farmers was recorded 9.46 tonnes and average productivity was found 12.21 tonnes ha-1. The highest quantity of potato waste was observed during planting and post-harvest periods. Proper planting date, frequency of irrigation, full ripening, keeping in standard storages and separating injured potatoes were the most important factors effective in waste reduction.